Placenta-Enriched LincRNAs MIR503HG and LINC00629 Decrease Migration and Invasion Potential of JEG-3 Cell Line - Muys, Bruna Rodrigues; Lorenzi, Júlio Cesar Cetrulo; Zanette, Dalila Luciola; Bueno, Rafaela de Barros Lima e; Araújo, Luíza Ferreira de; Dinarte-Santos, Anemari Ramos; Alves, Cleidson Pádua; Ramão, Anelisa; Molfetta, Greice Andreotti de; Vidal, Daniel Onofre; Silva, Jr., Wilson Araújo (PLOS ONE, 2016)
LINC00629 and MIR503HG are long intergenic non-coding RNAs (lincRNAs) mapped on chromosome X (Xq26), a region enriched for genes associated with human reproduction. Genes highly expressed in normal reproductive tissues and cancers (CT genes) are well known as potential tumor biomarkers. This study aimed to characterize the structure, expression, function and regulation mechanism of MIR503HG and LINC00629 lincRNAs. According to our data, MIR503HG expression was almost exclusive to placenta and LINC00629 was highly expressed in placenta and other reproductive tissues. Further analysis, using a cancer cell lines panel, showed that MIR503HG and LINC00629 were expressed in 50% and 100% of the cancer cell lines, respectively. MIR503HG was expressed predominantly in the nucleus of JEG-3 choriocarcinoma cells. We observed a positively correlated expression between MIR503HG and LINC00629, and between the lincRNAs and neighboring miRNAs. Also, both LINC00629 and MIR503GH could be negatively regulated by DNA methylation in an indirect way. Additionally, we identified new transcripts for MIR503HG and LINC00629 that are relatively conserved when compared to other primates. Furthermore, we found that overexpression of MIR503HG2 and the three-exon LINC00629 new isoforms decreased invasion and migration potential of JEG-3 tumor cell line. In conclusion, our results suggest that lincRNAs MIR503HG and LINC00629 impaired migration and invasion capacities in a choriocarcinoma in vitro model, indicating a potential role in human reproduction and tumorigenesis. Moreover, the MIR503HG expression pattern found here could indicate a putative new tumor biomarker.